2018
DOI: 10.1002/elsc.201700120
|View full text |Cite
|
Sign up to set email alerts
|

The chemo enzymatic functionalization of chitosan zeolite particles provides antioxidant and antimicrobial properties

Abstract: Silicate‐based microporous materials like zeolites are nano enabled particles and used for various applications including pharmaceutical formulations. This study reports on the chemo‐enzymatic functionalization of chitosan‐zeolite particles (CTS‐zeolites) with caffeic acid (CA) and glucose oxidase (GOX) to impart combined antioxidant and antimicrobial properties. CA was grafted on the chitosan moieties by using laccase generating stable particles (zeta potential –36.7 mV) of high antioxidant activity (44% DPPH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…While numerous reports exist describing the utilization of GOx in biomedical applications, such as in biosensing (typically at very low concentrations), cancer therapy, and antimicrobial therapy, , few articles report the direct assessment of its toxicity. The toxicity of GOx toward healthy mammalian cells in the presence of glucose is seldom discussed in the context of antimicrobial applications but is widely discussed in the context of tumor starvation, wherein this issue has recently been addressed by the use of antioxidant GOx-modified nanoparticles reported by Chen et al In one example of tumor therapy, Anraku, Osada, and Kataoka et al reported the preparation of pH- and H 2 O 2 -responsive vesicles loaded with GOx as smart therapeutic antitumor agents .…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While numerous reports exist describing the utilization of GOx in biomedical applications, such as in biosensing (typically at very low concentrations), cancer therapy, and antimicrobial therapy, , few articles report the direct assessment of its toxicity. The toxicity of GOx toward healthy mammalian cells in the presence of glucose is seldom discussed in the context of antimicrobial applications but is widely discussed in the context of tumor starvation, wherein this issue has recently been addressed by the use of antioxidant GOx-modified nanoparticles reported by Chen et al In one example of tumor therapy, Anraku, Osada, and Kataoka et al reported the preparation of pH- and H 2 O 2 -responsive vesicles loaded with GOx as smart therapeutic antitumor agents .…”
Section: Results and Discussionmentioning
confidence: 99%
“…For example, very recently, antimicrobial GOx-immobilized chitosan nanoparticles co-loaded with magnetic nanoparticles have been designed, which showed a six-log reduction in viable planktonic Staphyloccocus aureus, as well as showing magnetic properties for simple separation of these agents from the media . Similarly, GOx- and caffeic acid-functionalized chitosan-coated zeolite particles showed both antimicrobial and anti-inflammatory properties . Peroxide-producing enzymes have an advantage over other antimicrobial enzymes in that they typically have low-molecular-weight substrates, such as glucose, and do not require direct contact with bacteria to facilitate their antimicrobial mechanism, making them suitable for noncovalent encapsulation within semipermeable nanoparticles to form nanoreactors.…”
Section: Introductionmentioning
confidence: 99%
“…Zeolites are inorganic crystalline aluminosilicates with a porous structure on the micro-and nanoscale and high internal surface area, and they are well known as adsorbents, molecular sieves and ion exchange materials in many applications [7,8]. In the medical and pharmaceutical fields, zeolites have recently emerged as promising materials due to their bioactive properties and good stability in biological environments [9,10]. Many zeolites occur in nature as aluminosilicate minerals and more than 200 synthetic zeolites can be prepared in the laboratory [11].…”
Section: Introductionmentioning
confidence: 99%
“…The polysaccharides were modified with phenolic acids (gallic [ 314 ], caffeic [ 314 , 315 ], and ferulic [ 316 ]) in the presence of laccase as a catalyst. Chitosan molecules functionalized with phenolic acids showed much higher antioxidant activity in scavenging the radical cations 2,2′-Azino-bis-(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) [ 314 ] and 2,2-diphenyl-1-picrylhydrazyl (DPPH) [315 and, under certain modification conditions, a higher antimicrobial activity against E. Coli , as well as antifungal activity against C. albicans [ 314 ].…”
Section: Chemical Chemo-enzymatic and Enzymatic Functionalization Of Polysaccharidesmentioning
confidence: 99%
“…Tegl [ 315 ] demonstrated a chemo-enzymatic functionalization with glucose oxidase as a modifying reagent of particles of chitosan–zeolite and chitosan–zeolite modified with caffeic acid. Chitosan–zeolite particles modified with caffeic acid and then glucose oxidase demonstrated enhanced combined antioxidant and antimicrobial activity compared to the polysaccharide without modifications.…”
Section: Chemical Chemo-enzymatic and Enzymatic Functionalization Of Polysaccharidesmentioning
confidence: 99%